Principles of an integrated environment organization - Kovalov, Y. (Theory and practice of design, 2016)
The psychological comfort of man depends of the environment integrity, which has both geometric and associative components. As the result of historical examples of environment organizations analysis, 4 geometric and 3 associative principles of an integrated environment organization were formulated. The application of these principles refers to all levels of the structure of an environment, as well as different initial conditions of the problem of the environment organization.